생물학적 재생기법이 적용된 제올라이트계 여재의 저농도 암모니아성 질소 처리 - 김진수; 이지영; 김수진; 강민구; 박종택; 양창환; 이상일 (한국수처리학회지, 24(6), 2016)
This study was conducted to removal of low ammonia nitrogen. ball-type zeolites were used to adsorb ammonia nitrogen and regenerated simultaneously by attached nitrifiers. Prior to main experiment, adsorption rate and amount of adsorption was confirmed by pseudo second-order kinetic model and Freundlich, Langmuir isotherm models. Comparison of normal ball-type zeolite and nitrifiers-attached ball-type zeolite were proceeded in order to evaluate for nitrification(biological regeneration). And continuous operating experiment was operated in 1.6 L reactor at empty bed contact time(EBCT) 25 minute to check the possibility of continuous operation. In the result of experiment, only nitrifiers-attached ball-type zeolite was occurred nitrification(biological regeneration). And continuous operating experiment result during 32 days, it could constantly adsorbed the ammonia nitrogen during operating time. KCI Citation Count: 0